Process Evaluation of a University English Blended Learning Program; [Evaluación de Proceso de Un Programa Universitario de Inglés Mediante Blended Learning] - Ubeda-Menichetti, R; Urzua-Martinez, S; Aranda-Gengler, R (Ibero-American Association for Distance Higher Education (AIESAD), 2019)
In the context of current globalization, universities face demands for internationalization that involve providing students training oriented to the development of professional skills, among which the acquisition of a second language has a central importance. In the last few years, the University of Santiago de Chile has implemented a program of English Blended Learning in arcareers of eight faculties, whose objective is to develop linguistic and communicative skills at an intermediate level. For this purpose, the program consists of three pedagogical components: classrooms lessons, tutoring and an on-line platform. At the end of 2017 and the beginning of 2018, a process evaluation was carried out that sought to know, from the perspective of those immediately involved, how the program had been implemented, emphasizing the progress towards the fulfillment of its objectives. The data collection considered three techniques: a survey about the learning experience of the students (N = 780), a focus group with the teachers of the program and semi-structured interviews with coordinators or heads of the University. The main findings show a positive evaluation of the program when each component is observed by itself. However, the analysis of the integration between these reveals four critical tensions related to: the guidance on autonomous work, the managing of the assignment of tutorials, the transition from the pedagogical contents of the platform to the class and the functional differentiation between the components of the program. © 2019, Ibero-American Association for Distance Higher Education (AIESAD). All rights reserved.
Keywords: didactic use of the computer; higher education; tefl; education research; learner autonomy